The Role Of Mental Guidance Of The Air Force To Prevent Criminal Violations And Soldier Discipline In Order To Support The Air Force's Duties - Fardiansah, Ridwan; DAW, Martinus; Hendra, Afrizal (CV RIFAINSTITUT, 2025)
Mental coaching in an effort to prevent criminal and disciplinary violations among Indonesian Air Force soldiers is seen as one of the key elements in shaping the character and morale of soldiers, which in turn has a direct impact on performance and compliance with regulations. This study analyzes various forms of mental coaching implemented in the TNI AU environment, as well as their effectiveness in reducing incidents of legal and disciplinary violations. Through a qualitative approach with a case study method, data were collected from in-depth interviews, observations, and analysis of related documents. The results of the study indicate that systematic and ongoing mental coaching has a significant impact in reducing the number of violations among soldiers. In addition, this study found that mental coaching not only helps in preventing violations, but also plays a role in improving the morale and work ethics of soldiers, which is very important in supporting the main tasks of the TNI AU. This study recommends increasing the intensity and quality of mental coaching programs in the TNI AU environment, as well as its integration with other training programs to form soldiers with strong character and high discipline. Thus, mental coaching has been proven to be one of the effective strategies in maintaining the professionalism and integrity of TNI AU soldiers in carrying out their duties.